Identification of Optimal Reference Genes for Normalization of RT-qPCR Data in Cancerous and Non-Cancerous Tissues of Human Uterine Cervix. (16th March 2017) - Tan, Shing Cheng; Ismail, Mohd Pazudin; Duski, Daniel Roza; Othman, Nor Hayati; Bhavaraju, Venkata Murali Krishna; Ankathil, Ravindran
ABSTRACT: This study aimed to identify the most stably expressed reference genes from a panel of 32 candidate genes for normalization of reverse transcription-quantitative real-time polymerase chain reaction data in cancerous and non-cancerous tissues of human uterine cervix. Overall, PUM1, YWHAZ, and RPLP0 were identified as the most stably expressed genes in paired cancerous and non-cancerous tissues. The results were further stratified by the state of malignancy of the tissues, histopathological type of the cancer, and the human papillomavirus-type.